Commercial Monopoly or Open Research: China’s National Knowledge Infrastructure - Fan, Lijun; Yang, Lili (International Higher Education, 2022)
Developing research databases is a double-edged sword. Research databases may promote knowledge exchange, but their monopolistic/oligarchist practices are also building walls. Taking as an example the largest research database in China, the China National Knowledge Infrastructure, this article discusses the growing boycotts against the commercial monopoly of research databases in academia and reflects on the future of open research. It calls for concerted efforts from the whole research community.